Women’s experiences with the healthcare system during and after a late miscarriage: a qualitative meta-synthesis - Kristiansen, Wictoria; Mæhlum, Birgitte; Thimm, Jens C. (Frontiers in Psychiatry, 2026)
IntroductionMiscarriage is a relatively common pregnancy outcome and often imposes a significant psychological burden on those affected. Previous research suggests that the role of the healthcare system can greatly influence the psychological consequences of a miscarriage. Several literature reviews have addressed women’s experiences with the healthcare system in relation to early miscarriage. Late miscarriage, however, has received less attention in the research literature. The aim of this study was to synthesize qualitative literature on women’s experiences with healthcare in relation to late miscarriage.MethodsThe study is a qualitative meta-synthesis based on a systematic literature review conducted across four databases (CINAHL, Embase, Medline, and PsycInfo). Eight qualitative studies, comprising a total of 95 female participants, met the inclusion criteria and were included in the meta-synthesis. The data were analyzed using a meta-ethnographic approach.ResultsThe analysis identified three interconnected main themes that center on validating women’s emotional and practical needs of the women: (1) Acknowledgment of the loss, (2) The power of language, and (3) Institutional factors. The women emphasized that healthcare professionals should recognize and validate their loss, demonstrate empathy and compassion and provide clear, comprehensible information delivered sensitively. Hospital facilities and other systemic factors also had a significant impact on how the women felt cared for and supported.DiscussionThe study findings suggest areas for improving care and follow-up measures for those who experience late miscarriage. Further research on the topic could enhance understanding and contribute to the development of improved healthcare interventions for those affected. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier#CRD42024584350.